The Pembelajaran Gerak Dasar guna meningkatkan motoric kasar pada siswa SD Muhammadiyah Kebagusan - tommi, tommi maulana (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail, 2024)
The aim of holding this service is to improve gross motor skills in children. The service team provides stimulus by providing service to improve motor skills in children. This is done to increase knowledge about gross motor movements in children, where gross motor movements are very important for the development of children's movements at an early age. The method used in this service is lecture and practice methods. This is done to provide education about the importance of the basic movements of running, walking and jumping. Participants in this service were 4th grade students and students from SD Muhammadiyah Kebagusan, totaling 26 people who took part in this service. This service is carried out by providing material about motor movements and providing games that stimulate gross motor skills in children.